Transplantation of bone marrow-derived mesenchymal stem cells (BMSCs) improves brain ischemia-induced pulmonary injury in rats associated to TNF-α expression. Issue 1 (December 2016) - He, Qin-qin; He, Xiang; Wang, Yan-ping; Zou, Yu; Xia, Qing-jie; Xiong, Liu-Lin; Luo, Chao-zhi; Hu, Xiao-song; Liu, Jia; Wang, Ting-hua
Abstract Background Bone marrow mesenchymal stem cell (BMSCs)-based therapy seems to be a promising treatment for acute lung injury, but the therapeutic effects of BMSCs transplantation on acute lung injury induced by brain ischemia and the mechanisms have not been totally elucidated. This study explores the effects of transplantation of BMSCs on acute lung injury induced by focal cerebral ischemia and investigates the underlying mechanism. Methods Acute lung injury model was induced by middle cerebral artery occlusion (MCAO). BMSCs (with concentration of 1 × 106 /ml) were transplanted into host through tail vein 1 day after MCAO. Then, the survival, proliferation and migration of BMSCs in lung were observed at 4 days after transplantation, and histology observation and lung function were assessed for 7 days. Meanwhile, in situ hybridization (ISH), qRT-PCR and western blotting were employed to detect the expression of TNF-α in lung. Results Neurobehavioral deficits and acute lung injury could be seen in brain ischemia rats. Implanted BMSCs could survive in the lung, and relieve pulmonary edema, improve lung function, as well as down regulate TNF-α expression. Conclusions The grafted BMSCs can survive and migrate widespread in lung and ameliorate lung injury induced by focal cerebral ischemia in the MCAO rat models. The underlying molecular mechanism, at least partially, is related to the suppression of TNF-α.